Formation Mechanism and Evolutionary Laws of Well-Being at Work Among the New Generation of Construction Workers in China - Yunpeng Hu; Guanghui Tian; Lan Gao; Yangyang Yu; Guodong Ni (Buildings)
Improving well-being at work is crucial for increasing employment among construction workers and ensuring the healthy and sustainable development of China’s construction industry. Construction workers generally experience insufficient sleep, heavy workloads, work–family conflict, etc. At present, the new generation of construction workers (NGCWs) born after 1980 is gradually becoming the main force at construction sites in China. The value concepts, life attitudes, and personality traits of this group are significantly different from those of the older generations. Given the generational differences among construction workers, this study focuses on the formation mechanism and explores the evolutionary laws of well-being at work among NGCWs. In-depth interviews with 23 new-generation construction workers were conducted, and data analysis followed a three-step coding process based on grounded theory. Then, a three-stage formation mechanism model was constructed through continuous analysis. Finally, the casual and stock–flow diagrams were drawn and simulated on the basis of the system dynamics. The results indicated that well-being at work was directly influenced by internal work motivation. Both individual characteristics and the external environment played a role in shaping work motivation; however, the key difference lay in the fact that the external environment impacted internal work motivation through the mediation of individual-environment matching. Moreover, enhanced well-being at work led to a higher level of workers’ internal needs, which, in turn, further increased the complexity of individual-environment matching. Meanwhile, individual characteristics affected the process by which motivation was transformed into well-being at work. The level of well-being showed an upward tendency under the synergistic influence of different factors; the increasing rate was high and subsequently low. Furthermore, salary, job competence, and belonging needs can significantly affect well-being at work. These findings provide theoretical support and practical references to China’s construction companies and government departments for the purpose of improving NGCWs’ well-being at work.